Administrative responsibility for violation of flight security rules - Гончарук, Степан Тихонович; Гончаренко, Аліна Павлівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
In the article examines the administrative responsibility for violation of flight security rules, analyzes legal staff of this offense, expresses some remarks and suggestions